A new single-stage current source inverter for photovoltaic and fuel cell applications using reverse blocking IGBTs - Klumpner, Christian (2007)
Renewable energy sources such as photovoltaics (PVs) or fuel cells (FCs) are not fitted for direct power grid connection because they deliver DC voltage and current. This is why a power electronic interface is needed, consisting usually of a current-mode operated step-up DC/DC converter with/without isolation that boosts the voltage at a level that can be processed by a DC/AC inverter. This paper presents the implementation of a three-phase power electronic interface for PV/FCs that uses a single conversion stage approach based on a current source inverter (CSI) topology that would need only six reverse blocking IGBTs. In order to overcome the poor switching behavior of this device, a new way of implementing the CSI is proposed, which is proved to be more efficient. A new cost-effective CSI topology for multiple DC sources independently controlled is also proposed.The performance is assessed both in simulation and experimental.